GENRE BASED APPROACH TO TEACHING NARRATIVE WRITING - Zurdianto Zurdianto (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
This study aims at investigating the process of writing narrative text at lower secondary level of education (SMPN 4 Pekanbaru, Riau Province). The researcher, assisted by an English teacher as his collaborator, employed classroom action research to observe teaching and learning process. The study was conducted within two Cycles in which each Cycle comprised modeling, joint construction, and independent construction. Four instruments consisting of observation sheet, field notes, interview, and test were used to collect the data in Cycle 1. Five instruments consisting of observation sheet, field notes, interview, test, and questionnaire were used to collect the data in Cycle 2. The finding shows that three steps of writing narrative text to enhance the students’ learning atmosphere and improve the students’ writing achievement included (1) the students determined the important information from the text; (2) the students shared their ideas about their works with their friends; and (3) the students presented the texts in the class and discussed them with their classmates. Genre-based approach has been proved to enhance joyful learning atmosphere and improve the students’ learning writing achievement in classification text. Another finding is all participants customarily went through the basic phases of the writing process of narrative text: prewriting, drafting, revising and most of the them only know the terms like generic structure of the text. Besides, Interview in Cycle 1 revealed that the students felt comfortable, happy, and enjoyed learning writing using genre-based approach. Interview in Cycle 2 revealed that genre-based approach was comfortable, helpful to get outline of information, and an easy way to comprehend the text. Questionnaire indicated out of 35 students, 20 students’ responses were “strongly agree” and 15 responses were “agree” for the benefit of genre-based approach implementation. The finding of the students’ writing achievement showed that out of 35 students, 19 students got the score above 60 in Cycle 1; meanwhile, all students got the score above 60 in Cycle 2.